On the measurability of consciousness - Pradhan, Satya (Frontiers in Psychology, 2025)
With the recent advances in neuroscience and brain scanning technologies, there is an increased interest in the measurement problem of consciousness (MPC). The development of a consciousness measurement system (CMS) is still in its infancy without a formal framework and established design approach. This article presents a novel consciousness measurement framework based on consciousness theories and engineering concepts such as measurement workflow, problem space analysis, and observability. The framework proposes measurability criteria, applies them to different use cases, and identifies whether existing theories and technologies can measure consciousness attributes for specific use cases. Researchers and engineers can use this framework to determine the feasibility of CMS for individual use cases.